Gene Expression in Peripheral Immune Cells following Cardioembolic Stroke Is Sexually Dimorphic - Stamova, Boryana; Jickling, Glen C.; Ander, Bradley P.; Zhan, Xinhua; Liu, DaZhi; Turner, Renee; Ho, Carolyn; Khoury, Jane C.; Bushnell, Cheryl; Pancioli, Arthur; Jauch, Edward C.; Broderick, Joseph P.; et al. (PloS one, 2014)
Epidemiological studies suggest that sex has a role in the pathogenesis of cardioembolic stroke. Since stroke is a vascular disease, identifying sexually dimorphic gene expression changes in blood leukocytes can inform on sex-specific risk factors, response and outcome biology. We aimed to examine the sexually dimorphic immune response following cardioembolic stroke by studying the differential gene expression in peripheral white blood cells. Blood samples from patients with cardioembolic stroke were obtained at ≤3 hours (prior to treatment), 5 hours and 24 hours (after treatment) after stroke onset (n = 23; 69 samples) and compared with vascular risk factor controls without symptomatic vascular diseases (n = 23, 23 samples) (ANCOVA, false discovery rate p≤0.05, |fold change| ≥1.2). mRNA levels were measured on whole-genome Affymetrix microarrays. There were more up-regulated than down-regulated genes in both sexes, and females had more differentially expressed genes than males following cardioembolic stroke. Female gene expression was associated with cell death and survival, cell-cell signaling and inflammation. Male gene expression was associated with cellular assembly, organization and compromise. Immune response pathways were over represented at ≤3, 5 and 24 h after stroke in female subjects but only at 24 h in males. Neutrophil-specific genes were differentially expressed at 3, 5 and 24 h in females but only at 5 h and 24 h in males. There are sexually dimorphic immune cell expression profiles following cardioembolic stroke. Future studies are needed to confirm the findings using qRT-PCR in an independent cohort, to determine how they relate to risk and outcome, and to compare to other causes of ischemic stroke.